2021
DOI: 10.1038/s41419-021-03996-y
|View full text |Cite
|
Sign up to set email alerts
|

DHA exhibits synergistic therapeutic efficacy with cisplatin to induce ferroptosis in pancreatic ductal adenocarcinoma via modulation of iron metabolism

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is an extremely lethal cancer with limited treatment options. Cisplatin (DDP) is used as a mainstay of chemotherapeutic agents in combination with other drugs or radiotherapy for PDAC therapy. However, DDP exhibits severe side-effects that can lead to discontinuation of therapy, and the acquired drug resistance of tumor cells presents serious clinical obstacles. Therefore, it is imperative to develop a more effective and less toxic therapeutic strategy. We and others hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
74
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 112 publications
(75 citation statements)
references
References 44 publications
1
74
0
Order By: Relevance
“…Small molecule erastin was first discovered for specifically inducing ferroptosis in RAS mutant tumor cells, while sparing litter cytotoxicity to the non-malignant normal cells. Subsequently, RSL3, sorafenib, artemisinin and other molecules were identified for the ability to induce ferroptosis [ 29 , 36 , 37 ]. In the present work, we found that DSF/Cu, a FDA-approved clinical anti-alcoholism drug, selectively attenuates the abilities of proliferation, migration, invasion and angiogenesis in HCC cells at a low concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Small molecule erastin was first discovered for specifically inducing ferroptosis in RAS mutant tumor cells, while sparing litter cytotoxicity to the non-malignant normal cells. Subsequently, RSL3, sorafenib, artemisinin and other molecules were identified for the ability to induce ferroptosis [ 29 , 36 , 37 ]. In the present work, we found that DSF/Cu, a FDA-approved clinical anti-alcoholism drug, selectively attenuates the abilities of proliferation, migration, invasion and angiogenesis in HCC cells at a low concentration.…”
Section: Discussionmentioning
confidence: 99%
“…However, acquired drug resistance and high toxicity lead to the discontinuation of therapy. Our recent study demonstrated that dihydroartemisinin could effectively optimize the antitumor activity of cisplatin, and significantly reduced its effective concentrations (Du et al, 2021). Therefore, it's interesting to explore whether TEOA could be a promising adjuvant to improve the chemotherapy or overcome the chemoresistance of pancreatic cancer in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Artesunate exhibited cytotoxic effects, and its internalization in retinoblastoma cells was dependent on the expression of TfR1 at the membrane [ 47 ]. Increasing evidence suggests that dihydroartemisinin (DHA), a clinically used antimalarial agent, exhibits anticancer activity in numerous cancer cells [ 48 , 49 ]. DHA treatment resulted in iron deficiency by decreasing the expression of cell-surface TfR1 through an endocytic pathway [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence suggests that dihydroartemisinin (DHA), a clinically used antimalarial agent, exhibits anticancer activity in numerous cancer cells [ 48 , 49 ]. DHA treatment resulted in iron deficiency by decreasing the expression of cell-surface TfR1 through an endocytic pathway [ 48 , 49 ]. Sulfasalazine, an anti-inflammatory drug, is extensively used in chronic, long-term therapy of inflammatory bowel disease (ulcerative colitis) and rheumatoid arthritis.…”
Section: Discussionmentioning
confidence: 99%